DEVELOPMENT OF HIGH-END SEAPLANE PRODUCTS AND SERVICES: EVALUATION THROUGH SWOT ANALYSIS - Daniel Dewantoro; Dede Ardian; Demmy Setyo Wiyono; Genny Luhung Prasojo (Kultura: Jurnal Ilmu Hukum, Sosial, dan Humaniora, 2024)
The purpose of this study was to evaluate the development potential of products and services in the context of high-end seaplane services using SWOT analysis. The research identifies strengths and weaknesses in customer experience, safety aspects, route flexibility, and comfort offered by high-end seaplane services. The results of the SWOT analysis provide insight into product and service development strategies that can be applied to enhance competitiveness and expand market share in the high-end seaplane service industry. This research uses SWOT analysis to evaluate the strengths, weaknesses, opportunities, and threats in the context of high-end seaplane services. The strengths of high-end seaplane products and services include comfort, luxury, safety, and customer satisfaction. Furthermore, the study identifies product and service development opportunities, such as growing demand in luxury tourism and potential new market segments. The conclusions of this study provide a summary of the findings and implications for the development of high-end seaplane services. The study also suggests the scope of further research to further the understanding of the industry. Overall, this research contributes to the development of effective strategies to strengthen the position of high-end seaplanes in the global aviation industry.